POLE-mutated endometrial cancer: new perspectives on the horizon? - Fanale, Daniele; Corsini, Lidia Rita; Piraino, Paola; Pedone, Erika; Brando, Chiara; Bazan Russo, Tancredi Didier; Ferraro, Pietro; Simone, Alisia; Contino, Silvia; Prestifilippo, Ornella; Randazzo, Ugo; Giurintano, Ambra; et al. (Frontiers in Oncology, 2025)
Endometrial carcinoma (EC) is one of the most common gynecological cancers showing a survival rate of 15-17% in the case of advanced disease. Based on the mutational burden and copy number alteration, EC is classified into four different molecular subgroups: POLE-mutated (ultramutated), microsatellite unstable (hypermutated), low copy number (endometrioid), and high copy number (serous-like). Despite the high tumor grading, the ultramutated subtype, accounting for about 8-10% of all ECs, showed favorable prognostic potential, enhanced immune response, and excellent clinical outcomes. Somatic POLE alterations have been found in 6-10% of ECs, whereas germline pathogenic variants have been reported only in 0.25-4% of cases. Germline POLE alterations are linked to genome instability and are associated with onset of hereditary tumors, including colorectal cancer and EC. Emerging data suggests that knowledge of POLE mutational status could be clinically important, as ultramutated ECs may be more likely to respond to immunotherapy. In this Review, we will investigate the role of germline/somatic POLE genetic alterations in EC, discussing the potential future theranostic applications and evaluating the benefit of performing a routine genetic testing, in order to adopt prevention and surveillance strategies in germline POLE mutation carriers.